Real-time assessment of triage nurse situational awareness (SA) using the situation awareness global assessment technique (SAGAT) - Abeer Abdulaziz Alfuraydi; Modi Al-Moteri (PLoS ONE, 2025)
Background The emergency department (ED) is a complex, unpredictable, and distraction-filled environment. Within these challenging conditions, triage nurses are tasked with quickly assessing, identifying, and prioritizing patients who require urgent interventions. Studies from other safety-critical fields, such as aviation and the military, have highlighted that situational awareness (SA) is a critical skill for optimizing human performance during time-sensitive situations. In these fields, limitations in SA have been identified as significant risks to safety. However, despite its importance, SA in the context of EDs has been largely overlooked. Endsley’s SA theory and the Situation Awareness Global Assessment Technique (SAGAT) provide a framework to evaluate SA in dynamic and complex workspaces. This study aims to assess SA during real-time triage processes of patients in EDs, utilizing Endsley’s SA model. Method An observational cross-sectional study was conducted to assess SA. Forty real-time triaging processes were observed and evaluated in two ED sites, using the SAGAT to measure SA levels. Results A total of 40 triage nurses participated in the study across two ED sites. The findings revealed that the perception of patient cues was significantly reduced by workload (p = 0.048) and stress (p = 0.025), while playing video games was associated with enhanced perception of patient cues (p = 0.014). Additionally, a significant negative correlation was observed between the perception of patient cues and comprehension, indicating a cognitive trade-off between these two SA levels. Only 10% (n = 4) of participants achieved a good SA score, emphasizing the need for improvement. Conclusion The results underscore the importance of understanding and improving situational awareness in triage nurses using Endsley’s SA model. These findings offer valuable insights for enhancing future practice, education, and research focused on optimizing situational awareness in emergency nursing.